Pendampingan Partisipatif Digital Marketing pada UMKM Keripik Berbasis Biopreneur di Desa Celawan sebagai Upaya Optimalisasi Potensi Ekonomi Desa - Rifaldy Yusliandi; Bunga Sausan Sabilla; Herly Febri Fathiha; Nur Azmi Rahmadhini; Zahratul Idami (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
Biopreneur-based MSME chip producers in Celawan Village utilize local food resources such as bananas and cassava as their main sources of production, but their economic potential has not been optimized due to weak business identity, low digital marketing literacy, and limited market access. This community service activity aims to describe participatory digital marketing assistance as an effort to optimize the economic potential of the village by strengthening bio-entrepreneur-based MSME chips. The method used is a participatory approach through field observation, direct assistance, and contextual education according to the needs of MSME actors. The assistance focuses on creating a business brand, improving hygienic food product packaging, digitizing business locations through Google Maps, and utilizing simple digital media as a marketing tool. The results of the activity showed an increase in MSME actors' awareness of the importance of business identity, product quality, and digital marketing in increasing the added value of local food products. This mentoring was considered capable of expanding business visibility and supporting the optimization of village economic potential in a sustainable manner.